Interfacial phenomena in core–shell nanocomposites of PDMS adsorbed onto low specific surface area fumed silica nanooxides: Effects of surface modification. (26th June 2015) - Klonos, P.; Sulym, I.Ya.; Kyriakos, K.; Vangelidis, I.; Zidropoulos, S.; Sternik, D.; Borysenko, M.V.; Kyritsis, A.; Deryło-Marczewska, A.; Gun'ko, V.M.; Pissis, P.
Abstract: Core–shell structured nanocomposites of polydimethylsiloxane (PDMS) adsorbed onto low specific surface area fumed silica nanoparticles were studied employing structure (nitrogen adsorption–desorption, IPSD), morphology (SEM), thermal (DSC) and dielectric (BDS) techniques. The study focuses on the effects of porosity characteristics on polymer structure and dynamics at the filler interface. To that aim, roughness and porosity characteristics of silica were modified, prior to polymer adsorption, with nanozirconia grafting. The initial particles (15–150 nm in diameter) were found to aggregate and disperse well in the volume of nanocomposites, while nanozirconia grafting resulted in increased volume of the voids. PDMS was adsorbed both in the inner space of the voids and onto external surfaces of the aggregates. According to BDS and DSC the fraction of polymer chains at interfaces increases with nanozirconia modification and the respective dynamics ( α int relaxation) and cooperativity are enhanced. The results were interpreted in terms of increasing of the number of polymer–particle contact points on the modified surfaces, as compared to the unmodified ones. Finally, the characteristics of interfacial polymer (fraction, dynamics, polarizability) were interpreted employing models which involve bimodal chain conformations and increased order (orientation) of the polymer chains at the interfaces. Graphical abstract: Highlights: Surface modification of silica increases the contact points with the polymer. Interfacial polymer and its dynamics are enhanced on modified silica surfaces. Particles surface and polymer topology dominate on interfacial dynamics. Interfacial characteristics can be well described in terms of bimodal conformations.